Structural components of the arenavirus Pichinde. - Vezza, A C (1977)
Purified Pichinde virions grown in monolayers of BHK-21 cells were found to contain three major species of virion proteins as described previously (Ramos et al., J. Virol. 10:661-667, 1972). Two of the proteins were glycosylated (G1, molecular weight = 64,000; G2, molecular weight = 38,000) and were present in similar proportions on the outer surface of the virions. A third protein (N, molecular weight = 66,000) was not glycosylated and, in association with the viral RNA species, was the major protein component of the viral nucleocapsids. An estimate of the approximate number of molecules of these three major proteins per virion was made. Minor amounts of other proteins were also routinely observed in Pichinde virus preparations. None of the three major protein species were phosphorylated to any significant exten, nor did they contain sulfated components. Two virion RNA species (L and S), but no 18S rRNA species, were detected in Pichinde virus preparations obtained from infected BHK-21 cells.